INNOVATIVE ASPECTS OF THE MEDICAL AND PSYCHOLOGICAL LONG-TERM REHABILITATION OF OLDAGED PATIENTS IN OUT-PATIENT CLINICS ON THE BASIC OF SPECIALIZED MEDICAL CENTRES - E. A. Leskovets; A. G. Lutaya (Вестник университета, 2020)
The innovative aspects of medical and psychological rehabilitation of the old-aged patients in out-patient clinics on the basis of specialized medical centre have been studied. As an innovation: the long-term rehabilitation work (an additional period to the main course of 14 days) on the recovery of this category of patients, taking their age peculiarities into consideration (low level of intellectual and neuro-dynamic abilities); restorative treatment in a 24-hour hospital on the basis of the multifactorial program have been offered. In both cases, the emphasis is made on the recovery in terms of the developed program “The territory of welfare”. It is a medical and psychological support of the elderly on the basis of the Rehabilitation Medical Center “RZD-Medicine”, Yekaterinburg. On the one hand, this program will give an opportunity to overcome the lack of the provision of medical and psychological services during outpatient treatment.On the other hand, the program will help to understand the necessity of the rehabilitation measures extension for the elderly patients on the basis of medical centers. This program as an approbation for including into a pilot project “The organization of a modern model of a long-term medical treatment for the elderly people based on the principles of interdisciplinary and inter-departmental interaction (The Territory of care)”and for reconsidering the practice of rehabilitation services for the elderly; it is a necessary measure for the prevention, training and activation of the internal resources of older people for their productive aging.